THE NEED TO REFORM FAMILY PROPERTY LEGISLATION IN PERU: TOWARD THE INCLUSION OF SINGLE-PERSON HOUSEHOLDS - Mendoza Vásquez, Enrique (2025)
The article analyzes how family structures in Peru have evolved and how Article 495 of the Civil Code does not adequately reflect this diversity. Currently, only 21.8% of family units in Peru correspond to the traditional family, while 61.4% adopt other forms, such as single-parent, same-sex, and blended families, and the current legislation remains focused onprotecting only traditional family units,excluding those who do not fit this model.The analysis of the Registry Court’s resolutions shows that Peruvian legislation maintains a strict interpretation, excluding those without a spouse or dependent children from patrimonial protection. Although there has been some flexibility since 2013, these decisions have not effectively addressed the lack of protection for single-person households, leading to legal uncertainty.The article compares Peruvian legislation with that of Mexico, Colombia, Argentina, and Brazil, where more inclusive approaches have been adopted to protect individuals withouttraditional family ties. These legislationsreflect better adaptation to contemporary social realities.The conclusion highlights the urgent need to reform the Peruvian Civil Code to include and adequately protect all family configurations, ensuring equitable access to patrimonialprotection and aligning with the principles of equality and non-discrimination enshrined in human rights.